Gadolinium enhanced MRI predicts clinical and MRI disease activity in relapsing-remitting multiple sclerosis. Issue 3 (March 1997) - Koudriavtseva, T; Thompson, A J; Fiorelli, M; Gasperini, C; Bastianello, S; Bozzao, A; Paolillo, A; Pisani, A; Galgani, S; Pozzilli, C
Abstract : The aim of the study was to evaluate the predictive power of baseline gadolinium (Gd) enhanced MRI in relation to subsequent clinical and MRI activity. Sixty eight patients with clinically definite relapsing-remitting multiple sclerosis had a baseline Gd enhanced MRI and were followed up clinically and by monthly Gd enhanced MRI for six months. The occurrence of relapses during the follow up period was predicted by the presence of at least one enhancing lesion on the baseline MRI (P < 0.05). The number and volume of enhancing lesions at baseline were significantly associated with both enhancing lesions observed during the follow up period (P < 0.0001) and the accumulation of abnormality on T2 weighted images (P < 0.0001). Moreover, the presence of three or more enhancing lesions at baseline scan was consistently associated with the development of permanent abnormalities on T2 weighted images six months later. The study suggests that the number and volume of Gd enhancing lesions at a single examination are strong short term predictors of subsequent clinical and MRI activity.